Dual surface modification method for lithium-rich layered positive electrode material

By double surface modification of lithium-rich layered positive electrode material, the passivation layer and VO2 cladding layer are formed, which solves the problem of inefficiency and performance attenuation of the material and significantly improves its electrochemical performance.

CN119774673APending Publication Date: 2025-04-08CHENGDU ADVANCED METAL MATERIALS IND TECH RES INST CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510065957.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Lithium-rich layered cathode materials have problems such as low efficiency, poor rate performance, capacity and voltage attenuation, and are difficult to meet the requirements of high energy density.

Method used

By double surface modification on the lithium-rich layered positive electrode material, surface passivation and VO2 coating are used to adopt vanadyl sulfate solution and alkaline solution to form a passivation layer and VO2 coating layer.

Benefits of technology

The first Coulomb efficiency, discharge specific capacity and cycling stability of the lithium-rich layered cathode material are significantly improved, and lattice oxygen release and interface side reactions are suppressed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774673A_ABST
    Figure CN119774673A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of new energy, and provides a dual surface modification method for a lithium-rich layered positive electrode material. The method comprises the following steps: taking a lithium-rich layered positive electrode material sample, adding the lithium-rich layered positive electrode material sample into a pre-prepared vanadyl sulfate solution, and uniformly stirring to enable the lithium-rich layered positive electrode material sample and the vanadyl sulfate solution to react to obtain a mixed solution; adding an alkaline solution into the mixed solution, adjusting the pH value of the mixed solution to 7-10, and continuously stirring until the reaction is sufficient; filtering, washing and drying the fully reacted solution to obtain a lithium-rich layered positive electrode material precursor with a passivated surface and a VO2 coating; and heating the lithium-rich layered positive electrode material precursor to 400-700 DEG C in an inert gas atmosphere, and then carrying out heat preservation and furnace cooling to obtain the lithium-rich layered positive electrode material with a passivation layer and a VO2 coating layer on the surface. According to the method, surface passivation and surface coating of the lithium-rich layered positive electrode material are synchronously realized, and a method which is simple in step, easy in reaction condition control, low in production cost and capable of being applied on a large scale is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy technology, and in particular to a method for double surface modification of lithium-rich layered positive electrode materials. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, long service life and low cost. The most commonly used positive electrode materials for lithium-ion batteries include spinel lithium manganese oxide (LiMn2O4), lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2) and high nickel positive electrode materials (such as NCM811). These positive electrode materials for lithium-ion batteries have low capacity and are difficult to meet the requirements of high energy density. Compared with the previous lithium-ion battery positive electrode materials, lithium-rich layered positive electrode materials have the advantages of high specific capacity (>250mAh / g), low cost and low toxicity. However, lithium-rich layered positive electrode materials have problems such as low first coulombic efficiency, poor rate performance, capacity and voltage attenuation.

[0003] In lithium-rich layered cathode materials, the Li-O-Li configuration of Li2MnO3 domain-like lattice oxygen participates in charge compensation, which can achieve ultra-high specific capacity. However, at high potentials (>4.45V vs Li / Li⁺), the kinetics and reversibility of oxygen redox processes are poor, which will cause local structural rearrangement, lattice oxygen release, structural decay and interface side reactions. During charging, the O ²⁻ Oxidation forms O2, and the bulk O2 is trapped in the vacancy clusters for stability, while the surface O2 escapes, causing Li / O loss, transition metal dissolution, and surface structure degradation, leading to capacity and voltage decay. In addition, the nucleophilic attack of oxygen free radicals and the catalytic action of high-valent transition metal ions will accelerate the decomposition of the electrolyte, forming an unstable CEI film and increasing the interfacial impedance. Therefore, the surface modification of lithium-rich layered cathode materials is extremely critical to improving their electrochemical performance.

[0004] At present, methods such as surface coating and surface passivation (including surface doping and surface reconstruction) can improve the electrochemical performance of lithium-rich layered cathode materials to a certain extent. Surface coating only acts as a physical barrier and has no functions such as absorbing oxygen and improving interfacial charge transfer. Although surface passivation alone stabilizes the surface structure, it cannot resist electrolyte corrosion. The effect of using the two alone to improve electrochemical performance is limited, and it is difficult to achieve surface coating and surface passivation simultaneously.

[0005] Therefore, a simple, low-cost and large-scale applicable dual surface modification method for lithium-rich layered cathode materials is urgently needed. Summary of the invention

[0006] In view of the difficulty in simultaneously achieving surface passivation and coating of lithium-rich layered positive electrode materials in the prior art, the present disclosure provides a method for dual surface modification of lithium-rich layered positive electrode materials to improve their electrochemical performance.

[0007] According to a first aspect of the present invention, a method for double surface modification of a lithium-rich layered cathode material is provided, comprising: Step a, taking a lithium-rich layered positive electrode material sample, adding it to a pre-prepared vanadyl sulfate solution, stirring evenly to allow the two to react, and obtaining a mixed solution; Step b, adding an alkaline solution to the mixed solution, adjusting the pH value of the mixed solution to 7-10, and continuing to stir until the reaction is sufficient; Step c, filtering, washing and drying the fully reacted solution to obtain a lithium-rich layered positive electrode material precursor with a passivated surface and a VO2 coating; Step d: heating the lithium-rich layered cathode material precursor to 400-700° C. in an inert gas atmosphere, then keeping the temperature and cooling it with the furnace to obtain a lithium-rich layered cathode material having a passivation layer and a VO2 coating layer on the surface.

[0008] In some embodiments, the step a further comprises: A 0.1-1 mol / L vanadyl sulfate solution is prepared, and the pH value of the vanadyl sulfate solution is controlled to be 1-4.

[0009] In some embodiments, step a comprises: Take 50-200g of lithium-rich layered positive electrode material sample, add it into 100ml of pre-prepared vanadyl sulfate solution, stir the two evenly at 50-80°C and react for 5-20 minutes.

[0010] In some embodiments, step b comprises: Add an alkaline solution dropwise to the mixed solution until the pH value of the mixed solution is 7-10, and then continue stirring until the reaction is complete.

[0011] In some embodiments, step b comprises: Add an alkaline solution dropwise to the mixed solution until the pH value of the mixed solution is 7-10, then continue stirring and react for 1-6 hours to ensure sufficient reaction.

[0012] In some embodiments, step c comprises: The fully reacted solution is filtered, washed with deionized water and ethanol in turn, and then placed in a vacuum drying oven for drying to obtain a lithium-rich layered positive electrode material precursor with a passivated surface and VO2 coating.

[0013] In some embodiments, step c further comprises: The fully reacted solution was filtered, washed twice with deionized water and then twice with ethanol, and then placed in a vacuum drying oven and dried at 80°C to obtain a lithium-rich layered positive electrode material precursor with a passivated surface and VO2 coating.

[0014] In some embodiments, step d comprises: The lithium-rich layered cathode material precursor is heated to 400-700°C at a rate of 5°C / min in an inert gas atmosphere, then kept warm for 1-6 hours and then cooled in the furnace to obtain a lithium-rich layered cathode material with a passivation layer and a VO2 coating layer on the surface.

[0015] In some embodiments, the alkaline solution includes one or more of a sodium hydroxide solution, an ammonia solution, and a urea solution.

[0016] In some embodiments, the lithium-rich layered cathode material has a molecular formula of Li 1+x TM 1-x O2, wherein the TM is at least two of Ni, Co and Mn, and the value of x is 0 <x<1。

[0017] The above-mentioned method for double surface modification of lithium-rich layered positive electrode materials is to take a lithium-rich layered positive electrode material sample, add it to a pre-configured vanadyl sulfate solution, stir the two evenly to react, and obtain a mixed solution. Add an alkaline solution to the mixed solution, adjust the pH value of the mixed solution to 7-10, continue stirring until the reaction is sufficient, filter, wash and dry the fully reacted solution to obtain a lithium-rich layered positive electrode material precursor with a passivated surface and a VO2 coating, and then place it in an inert gas atmosphere and heat it to 400-700°C, then keep it warm and cool it with the furnace to obtain a lithium-rich layered positive electrode material with a passivation layer and a VO2 coating layer on the surface. The method for dual surface modification of lithium-rich layered positive electrode materials of the present application simultaneously realizes surface passivation and surface coating of lithium-rich layered positive electrode materials by a liquid phase method, provides a method with simple steps and easy-to-control reaction conditions, and the vanadyl sulfate solution and alkaline solution used are common chemical raw materials, with low production cost and large-scale application, which significantly inhibits the release of lattice oxygen and the occurrence of interfacial side reactions, thereby improving the first coulombic efficiency, discharge specific capacity and cycle stability of the lithium-rich layered positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.

[0019] Figure 1 A flow chart of a method for double surface modification of a lithium-rich layered positive electrode material provided in one embodiment of the present invention; Figure 2 A scanning electron microscope (SEM) morphology image of the lithium-rich layered positive electrode material obtained in accordance with Example 2 provided by the present invention; Figure 3 A scanning electron microscope (SEM) morphology image of the lithium-rich layered positive electrode material obtained in accordance with Example 6 provided by the present invention; Figure 4 The lithium-rich layered positive electrode material Li of Example 2, Comparative Example 1 and Blank Example 1 provided by the present invention 1.2 Ni 0.2 Mn 0.6 Schematic diagram of X-ray diffraction (XRD) pattern of O2; Figure 5 A comparison chart of the first charge and discharge curves of blank example 1 and comparative example 1 of embodiments 1-4 provided by the present invention at a rate of 0.1C; Figure 6 A comparison chart of the rate performance of Example 2, Blank Example 1 and Comparative Example 1 provided by the present invention; Figure 7 Capacity attenuation graph of blank example 1 and comparative example 1 of examples 1-4 provided by the present invention at 1C rate; Figure 8 The voltage decay diagram of blank example 1 and comparative example 1 of embodiments 1-4 provided by the present invention at a rate of 1C; Fig. 9 This is a capacity attenuation graph of Blank Example 2 and Comparative Example 2 of Examples 5-8 provided by the present invention at a 1C rate. DETAILED DESCRIPTION

[0020] The following is a further detailed description of the embodiments of the present disclosure in conjunction with the accompanying drawings and examples. The detailed description of the following embodiments and the accompanying drawings are used to exemplarily illustrate the principles of the present disclosure, but cannot be used to limit the scope of the present disclosure. The present disclosure can be implemented in many different forms and is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

[0021] The present disclosure provides these embodiments to make the present disclosure thorough and complete, and to fully express the scope of the present disclosure to those skilled in the art. It should be noted that unless otherwise specifically stated, the relative arrangement of the parts and steps, the composition of the materials, the numerical expressions and the numerical values ​​set forth in these embodiments should be interpreted as being merely exemplary, and not as limiting.

[0022] It should be noted that, in the description of the present disclosure, unless otherwise specified, the meaning of "multiple" is greater than or equal to two; the terms "upper", "lower", "left", "right", "inner", "outer", etc., indicating the orientation or positional relationship, are only for the convenience of describing the present disclosure and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present disclosure. When the absolute position of the object being described changes, the relative positional relationship may also change accordingly.

[0023] In addition, the words "first", "second" and similar words used in this disclosure do not indicate any order, quantity or importance, but are only used to distinguish different parts. The words "include" or "comprise" and similar words mean that the elements before the word include the elements listed after the word, and do not exclude the possibility of including other elements.

[0024] It should also be noted that in the description of the present disclosure, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the present disclosure can be understood according to the specific circumstances. When a specific device is described as being located between a first device and a second device, there may or may not be an intermediate device between the specific device and the first device or the second device.

[0025] All terms used in the present disclosure have the same meanings as those understood by those of ordinary skill in the art to which the present disclosure belongs, unless otherwise specifically defined. It should also be understood that terms defined in general dictionaries, for example, should be interpreted as having meanings consistent with their meanings in the context of the relevant technology, and should not be interpreted in an idealized or extremely formal sense, unless explicitly defined as such herein.

[0026] Technologies, methods, and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered part of the specification.

[0027] It should be understood that the embodiments of the present invention shown in the exemplary embodiments are only illustrative. Although only a few embodiments are described in detail in the present invention, it is easy for those skilled in the art to appreciate that multiple modifications are feasible without actually departing from the teaching of the subject matter of the present invention. Accordingly, all such modifications should be included within the scope of the present invention. Without departing from the gist of the present invention, other replacements, modifications, changes and deletions may be made to the design, operating conditions and parameters of the following exemplary embodiments.

[0028] Please refer to Figure 1 , Figure 1 The flowchart of the method for double surface modification of lithium-rich layered positive electrode materials provided by one embodiment of the present invention is shown. A method 100 for double surface modification of lithium-rich layered positive electrode materials comprises: Step a, taking a lithium-rich layered positive electrode material sample, adding it to a pre-prepared vanadyl sulfate solution, stirring evenly to allow the two to react, and obtaining a mixed solution; Specifically, the acidic characteristics of the vanadyl sulfate solution are utilized to convert the H + It is helpful to remove the residual alkali on the surface of the lithium-rich layered cathode material sample, which helps to improve the first coulomb efficiency, inhibit the release of CO2 gas, etc. Part of the Li / O on the surface of the particles of the lithium-rich layered cathode material is removed by acid etching, the surface of the particles is passivated and a passivation layer is generated. The passivation layer has the function of protecting the lithium-rich layered cathode material. The passivation layer can inactivate the lattice oxygen on the surface of the lithium-rich layered cathode material, thereby inhibiting oxygen overflow, surface structure rearrangement, and transition metal ion dissolution.

[0029] Step b, adding alkaline solution to the mixed solution, adjusting the pH value of the mixed solution to 7-10, and continuing to stir until the reaction is sufficient; Specifically, an alkaline solution is added to the mixed solution to adjust the pH value of the mixed solution, and the reaction time, temperature and other conditions are adjusted to adjust the thickness of the passivation layer on the particle surface of the lithium-rich layered positive electrode material.

[0030] Step c, filtering, washing and drying the fully reacted solution to obtain a lithium-rich layered positive electrode material precursor with a passivated surface and a VO2 coating; Specifically, the fully reacted solution is filtered, washed and dried to obtain a lithium-rich layered cathode material precursor with a passivated surface and a VO2 coating. The VO2 coating layer acts as a physical barrier to reduce the contact between the electrolyte and the lithium-rich layered cathode material and the occurrence of interface side reactions. At the same time, the VO2 coating layer can absorb the oxygen released by the lithium-rich cathode material during the first charge (corresponding to V 4+ Oxidized to V 5+ ), after which V2O5 can participate in the electrochemical reaction process (Li +embedded therein), thereby inhibiting the release of lattice oxygen from the positive electrode particles, reducing the occurrence of interfacial side reactions, significantly improving the first coulombic efficiency of the lithium-rich layered positive electrode material, and inhibiting voltage decay and capacity decay.

[0031] Step d: heating the lithium-rich layered cathode material precursor to 400-700° C. in an inert gas atmosphere, then keeping the temperature and cooling it with the furnace to obtain a lithium-rich layered cathode material having a passivation layer and a VO2 coating layer on the surface.

[0032] Specifically, the above steps are simple and the reaction conditions are easy to control, which is suitable for industrial continuous production, improves production efficiency and is suitable for large-scale production. At the same time, the vanadyl sulfate solution and alkaline solution used therein are common chemical raw materials, which are inexpensive, have low production costs, are easy to promote and apply, and can even be extended to the surface modification process of lithium-ion battery positive electrode materials such as lithium cobalt oxide and high-voltage spinel and sodium-ion battery layered oxide positive electrode materials.

[0033] The above-mentioned method for dual surface modification of lithium-rich layered positive electrode materials simultaneously realizes surface passivation and surface coating of lithium-rich layered positive electrode materials through a liquid phase method, providing a method with simple steps and easy-to-control reaction conditions. The vanadyl sulfate solution and alkaline solution used are common chemical raw materials, have low production costs and can be applied on a large scale. It significantly inhibits the release of lattice oxygen and the occurrence of interfacial side reactions, thereby improving the first coulombic efficiency, discharge specific capacity and cycle stability of the lithium-rich layered positive electrode material.

[0034] According to some embodiments of the present invention, before step a, the method further includes: preparing a 0.1-1 mol / L vanadyl sulfate solution, and controlling the pH value of the vanadyl sulfate solution to be 1-4.

[0035] Specifically, a 0.1-1 mol / L vanadyl sulfate solution is prepared and its pH value is controlled to be 1-4 to maximize the H + The residual alkali on the surface of lithium-rich layered cathode material samples can be removed, thereby improving the first coulombic efficiency and inhibiting the release of CO2 gas.

[0036] According to some embodiments of the present invention, step a includes: taking 50-200 g of a lithium-rich layered cathode material sample, adding it to a pre-prepared 100 ml vanadyl sulfate solution, stirring the two at 50-80° C. and reacting for 5-20 minutes.

[0037] Specifically, under appropriate temperature and reaction time, the lithium-rich layered cathode material sample can be fully reacted with the vanadyl sulfate solution.

[0038] According to some embodiments of the present invention, step b includes: adding alkaline solution dropwise to the mixed solution until the pH value of the mixed solution is 7-10, and then continuing to stir until the reaction is sufficient.

[0039] Specifically, adding the alkaline solution dropwise into the mixed solution can precisely control the degree of reaction and optimize the surface properties.

[0040] According to some embodiments of the present invention, step b includes: adding alkaline solution dropwise to the mixed solution until the pH value of the mixed solution is 7-10, and then continuing to stir and react for 1-6 hours to achieve sufficient reaction.

[0041] Specifically, continuing stirring and reacting for 1-6 hours can ensure sufficient reaction and avoid the problem of insufficient reaction.

[0042] According to some embodiments of the present invention, step c includes: filtering the fully reacted solution, washing it with deionized water and ethanol in sequence, and then placing it in a vacuum drying oven for drying to obtain a lithium-rich layered positive electrode material precursor with a passivated surface and a VO2 coating.

[0043] Specifically, using deionized water and ethanol for cleaning successively can remove impurity ions adsorbed on the surface of the material, residues such as unreacted chemical reagents, and make the surface of the material purer.

[0044] According to several embodiments of the present invention, step d includes: heating the lithium-rich layered positive electrode material precursor to 400-700°C at a rate of 5°C / min in an inert gas atmosphere, then keeping it warm for 1-6 hours and then cooling it with the furnace to obtain a lithium-rich layered positive electrode material with a passivation layer and a VO2 coating layer on the surface.

[0045] Specifically, operating under an inert gas atmosphere can prevent the material from chemically reacting with oxygen, water vapor, etc. in the air during the heating process, creating a stable and pure environment for the transformation and optimization of the material structure.

[0046] According to some embodiments of the present invention, the alkaline solution includes one or more of a sodium hydroxide solution, an ammonia solution, and a urea solution.

[0047] Specifically, sodium hydroxide solution, ammonia solution and urea solution as the alkaline solution used in the present invention are all common chemical raw materials, have low production costs and can be used on a large scale.

[0048] According to some embodiments of the present invention, the molecular formula of the lithium-rich layered positive electrode material is Li 1+x TM 1-x O2, wherein the TM is at least two of Ni, Co and Mn, and the value of x is 0 <x<1。

[0049] Specifically, lithium-rich layered cathode materials such as Li 1.2 Ni 0.2 Mn 0.6O2、Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2, etc.

[0050] In order to further understand the method for double surface modification of a lithium-rich layered positive electrode material of the present invention, it is further described in detail in the following specific examples.

[0051] Example 1 (1) Prepare 0.1 mol / L vanadium oxysulfate (VOSO4) solution, then take 85 g of lithium-rich layered cathode material Li 1.2 Ni 0.2 Mn 0.6 The O2 powder sample (prepared by the sol-gel method, with a particle size of 200-300 nm) was poured into 100 mL of the above-mentioned vanadyl sulfate solution, stirred evenly and reacted for 10 minutes in an oil bath at a temperature below 60°C to perform surface passivation to obtain a mixed solution.

[0052] (2) Add alkaline solution dropwise to the mixed liquid until the pH reaches 9, then continue stirring and react for 3 hours.

[0053] (3) After the reaction is complete, filter and wash, wash twice with deionized water, wash twice with ethanol, and dry it in a vacuum drying oven at 80°C overnight to obtain a lithium-rich layered positive electrode material precursor whose surface is passivated and has a VO2 coating on the particle surface.

[0054] (4) The precursor is placed in a tubular furnace, heated to 500°C at a rate of 5°C / min under an inert atmosphere, and then calcined for 5 hours. The precursor is then cooled in the furnace to obtain a double-surface-modified lithium-rich layered cathode material having a passivation layer and a VO2 coating layer on the surface.

[0055] Example 2 The difference from Example 1 is that 0.3 mol / L vanadyl sulfate (VOSO4) solution is prepared, and the other steps are the same and will not be repeated. The scanning electron microscope (SEM) morphology of the corresponding lithium-rich layered positive electrode material is as follows: Figure 2 As shown. Figure 2 It can be seen that the lithium-rich layered cathode material in Example 2 is a typical nanoparticle prepared by the sol-gel method, with a size of about 200-300 nm. At the same time, the surface of the particles is relatively rough and there are deposits on the surface, which may be a VO2 coating layer.

[0056] Example 3 The difference from Example 1 is that a 0.5 mol / L vanadyl sulfate (VOSO4) solution is prepared, and the other steps are the same and will not be repeated.

[0057] Example 4 The difference from Example 1 is that a 1 mol / L vanadyl sulfate (VOSO4) solution is prepared, and the other steps are the same and will not be repeated.

[0058] Example 5 (1) Prepare 0.1 mol / L vanadium oxysulfate (VOSO4) solution, then take 85 g of lithium-rich layered cathode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 An O2 powder sample (prepared by coprecipitation method, secondary particles of about 10 μm, composed of primary particles of 300-500 nm in size) was poured into 100 mL of the above-mentioned vanadyl sulfate solution, stirred evenly in an oil bath at a temperature below 60°C and reacted for 10 minutes to passivate the surface and obtain a mixed solution.

[0059] (2) Add alkaline solution dropwise to the mixed liquid until the pH reaches 9, then continue stirring and react for 3 hours.

[0060] (3) After the reaction is complete, filter and wash, wash twice with deionized water, wash twice with ethanol, and dry it in a vacuum drying oven at 80°C overnight to obtain a lithium-rich layered positive electrode material precursor whose surface is passivated and has a VO2 coating on the particle surface.

[0061] (4) The precursor is placed in a tubular furnace, heated to 500°C at a rate of 5°C / min under an inert atmosphere, and then calcined for 5 hours. The precursor is then cooled in the furnace to obtain a double-surface-modified lithium-rich layered cathode material having a passivation layer and a VO2 coating layer on its surface.

[0062] Example 6 The difference from Example 5 is that 0.3 mol / L vanadyl sulfate (VOSO4) solution is prepared, and the other steps are the same and will not be repeated. The scanning electron microscope (SEM) morphology of the corresponding lithium-rich layered positive electrode material is as follows: Figure 3 As shown. Figure 3 It can be seen that the lithium-rich layered positive electrode material in Example 6 is a typical secondary particle prepared by the co-precipitation method, with a secondary size of about 10 μm, which is assembled from nano-sized primary particles; it is worth noting that there is an obvious coating layer on the surface of the particles, which should be the VO2 coating layer, so the primary particles are covered and difficult to identify.

[0063] Example 7 The difference from Example 5 is that a 0.5 mol / L vanadyl sulfate (VOSO4) solution is prepared, and the other steps are the same and will not be repeated.

[0064] Example 8 The difference from Example 5 is that a 1 mol / L vanadyl sulfate (VOSO4) solution is prepared, and the other steps are the same and will not be repeated.

[0065] Blank example 1 The original lithium-rich layered cathode material Li without any treatment 1.2 Ni 0.2 Mn 0.6 O2.

[0066] Blank example 2 The original lithium-rich layered cathode material Li without any treatment 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.

[0067] Comparative Example 1 Comparative Example 1 is compared with Examples 1-4. In Comparative Example 1, only Li 1.2 Ni 0.2 Mn 0.6 The O2 powder sample was placed in a tubular furnace, heated to 500°C at a rate of 5°C / min in an inert gas atmosphere, and then calcined for 5 hours, followed by cooling with the furnace.

[0068] Comparative Example 2 Comparative Example 2 is compared with Examples 5-8. In Comparative Example 2, only Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 The O2 powder sample was placed in a tubular furnace, heated to 500°C at a rate of 5°C / min in an inert gas atmosphere, and then calcined for 5 hours, followed by cooling with the furnace.

[0069] Among them, the lithium-rich layered positive electrode material Li 1.2 Ni 0.2 Mn 0.6 The X-ray diffraction (XRD) pattern of O2 is as follows Figure 4 As shown, from Figure 4It can be seen that the lithium-rich layered positive electrode materials in Example 2, Comparative Example 1 and Blank Example 1 all show similar XRD patterns, and no other additional diffraction peaks appear, indicating that the surface modification process in the present invention will not affect the crystal structure of the lithium-rich layered manganese-based positive electrode material. In addition, the XRD pattern of Example 2 does not have a diffraction peak of VO2, indicating that the surface-coated VO2 is in an amorphous state or the coating amount is too small (about 3wt%) and there is no obvious diffraction peak.

[0070] The comparison of the first charge and discharge curves of Examples 1-4, Blank Example 1 and Comparative Example 1 at 0.1C rate is shown in the figure below: Figure 5 As shown, from Figure 5 It can be seen that compared with Blank Example 1 and Comparative Example 1, Examples 1-4 can obtain higher first coulombic efficiency and discharge specific capacity, indicating that double-layer surface modification can reduce interface side reactions and inhibit lattice oxygen release.

[0071] The rate performance comparison diagram of Example 2, Blank Example 1 and Comparative Example 1 is shown in the figure below: Figure 6 As shown, from Figure 6 It can be seen that the lithium-rich layered cathode material in Example 2 has the best rate performance, and its specific capacity at 5C is 145.7 mAh g -1 , higher than that of comparative example 1 (129.5 mAh g -1 ) and Blank 1 (120.3 mAh g -1 ), indicating that the double surface modification does not lead to a decrease in rate performance. On the contrary, it is precisely because of the improvement in surface stability caused by the double surface modification that the lattice oxygen release, the destruction of the bulk and surface structure, the dissolution of transition metals and the excessive growth of the cathode / electrolyte interface (CEI) are suppressed, ensuring the Li + The transmission path is unobstructed, thus showing better rate performance.

[0072] The capacity decay graphs of Examples 1-4, Blank Example 1 and Comparative Example 1 at 1C rate are shown in FIG. Figure 7 As shown, the voltage decay diagrams of Examples 1-4, Blank Example 1 and Comparative Example 1 at 1C rate are as follows Figure 8 As shown, from Figure 7-8 It can be seen that compared with Blank Example 1 and Comparative Example 1, the lithium-rich layered positive electrode materials of Examples 1-4 have better electrochemical cycle stability. Among them, the capacity retention rate of Example 2 after 200 cycles at 1C is 90.1%, and the voltage decay rate is only 0.78 mV cycle -1The surface passivation layer can inactivate the surface lattice oxygen, thereby inhibiting irreversible oxygen escape, surface structural rearrangement and transition metal ion dissolution; the VO2 coating layer can not only act as a physical barrier to reduce the contact between the electrolyte and the lithium-rich layered cathode material and the occurrence of interfacial side reactions, but also absorb the oxygen released by the lithium-rich cathode material during the first charge (corresponding to part of V 4+ Oxidized to V 5+ ), and then V2O5 can also participate in the electrochemical reaction process, significantly improving the first coulombic efficiency and cycle stability of the lithium-rich layered positive electrode material (the voltage decay and capacity decay are only 36% and 34% of the blank case, respectively).

[0073] The capacity decay graphs of Examples 5-8, Blank Example 2 and Comparative Example 2 at 1C rate are shown in FIG. Fig. 9 As shown, from Fig. 9 It can be seen that compared with Blank Example 2 and Comparative Example 2, the lithium-rich layered positive electrode materials of Examples 5-8 have better electrochemical cycle stability. Among them, the capacity retention rate of Example 6 after 200 cycles at 1C is 96.7%, which is much better than Blank Example 2 (67.1%) and Comparative Example 2 (75.4%). It shows that the dual surface modification method of the present invention is also applicable to cobalt-containing lithium-rich layered positive electrode materials, showing a certain versatility.

[0074] The lithium-rich layered positive electrode materials obtained in the above Examples 1-8, Blank Examples 1-2 and Comparative Examples 1-2 were mixed with a conductive agent (conductive carbon black super-P) and a binder (polyvinylidene fluoride, PVDF) at a mass ratio of 8:1:1 at room temperature in N-methylpyrrolidone (NMP), and then uniformly coated on an aluminum current collector, with an active material surface loading of 2.5-4.0 mg cm -2 , then dried, cut, rolled, and transferred to a glove box for storage. CR2032 button cells were assembled in an argon-filled glove box. The negative electrode was a metal lithium sheet, the diaphragm was a Celgard2400 diaphragm, and the electrolyte was 1.0 M LiPF6 dissolved in a mixture of EC:DMC:EMC. The mass fraction ratio of the three solvents was 1:1:1 wt%. The button cell was first activated at a current density of 0.1C (1C = 250mA / g). After activation, the charge and discharge cycle was performed at a current density of 1C, and the test voltage range was 2.0-4.8 V. The rate test was carried out in the order of 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C for 5 cycles each, and then restored to 0.1C.

[0075] Finally, the test results of the initial capacity, capacity after cycle and capacity retention rate corresponding to Examples 1-4, Blank Example 1 and Comparative Example 1 are shown in Table 1 below: Table 1

[0076] As can be seen from Table 1, compared with Blank Example 1 and Comparative Example 1, Examples 1-4 can obtain higher first coulombic efficiency and discharge specific capacity, which is due to the dual surface modification of the material (including surface passivation and VO2 surface coating). Among them, the lithium-rich layered positive electrode material of Example 2 has the best electrochemical performance, with an initial coulombic efficiency of 91.2% and a discharge specific capacity of up to 274.4 mAh g -1 After 200 cycles at 1C, the capacity retention rate is 90.1%, and the voltage decay rate is 0.78 mVcycle -1 The surface passivation layer can inactivate the surface lattice oxygen, thereby inhibiting irreversible oxygen escape, surface structural rearrangement and transition metal ion dissolution; the VO2 surface coating can not only serve as a physical barrier to reduce the contact between the electrolyte and the lithium-rich layered cathode material and the occurrence of interfacial side reactions, but also absorb the oxygen released by the lithium-rich cathode material during the first charge (corresponding to part of V 4+ Oxidized to V 5+ ), and then V2O5 can also participate in the electrochemical reaction process, significantly improving the first coulombic efficiency and cycle performance of the lithium-rich layered cathode material.

[0077] The test results of the initial capacity, capacity after cycle and capacity retention rate corresponding to Examples 5-8, Blank Example 2 and Comparative Example 2 are shown in Table 2 below: Table 2

[0078] As can be seen from Table 2, compared with Blank Example 2 and Comparative Example 2, Examples 5-8 can obtain higher first coulombic efficiency and discharge specific capacity, which is due to the dual surface modification of the material (including surface passivation and -VO2 surface coating). Among them, the lithium-rich layered positive electrode material of Example 6 has the best electrochemical performance, with an initial coulombic efficiency of 86.9% and a discharge specific capacity of up to 279.3 mAh g -1 After 200 cycles at 1C, the capacity retention rate is 96.7%, and the voltage decay rate is 1.18 mVcycle -1 .

[0079] From the measurement results in the above Examples 1-8, Comparative Examples 1-2 and Blank Examples 1-2, it can be seen that the surface passivation and surface coating of the lithium-rich layered positive electrode material are simultaneously achieved by the liquid phase method, which provides a method with simple steps and easy to control reaction conditions. The vanadium sulfate solution and alkaline solution used are common chemical raw materials, have low production costs and can be used on a large scale. The lattice oxygen release and interfacial side reactions are significantly inhibited, thereby improving the first coulombic efficiency, discharge specific capacity and cycle stability of the lithium-rich layered positive electrode material.

[0080] So far, various embodiments of the present disclosure have been described in detail. In order to avoid obscuring the concept of the present disclosure, some details known in the art are not described. Based on the above description, those skilled in the art can fully understand how to implement the technical solution disclosed here.

[0081] Although some specific embodiments of the present disclosure have been described in detail by way of examples, it should be understood by those skilled in the art that the above examples are for illustration only and are not intended to limit the scope of the present disclosure. It should be understood by those skilled in the art that the above embodiments may be modified or some technical features may be replaced by equivalents without departing from the scope and spirit of the present disclosure. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there is no structural conflict.

Claims

1. A method for double surface modification of lithium-rich layered positive electrode materials, characterized in that: include: Step a, taking a lithium-rich layered positive electrode material sample, adding it to a pre-prepared vanadyl sulfate solution, stirring evenly to allow the two to react, and obtaining a mixed solution; Step b, adding an alkaline solution to the mixed solution, adjusting the pH value of the mixed solution to 7-10, and continuing to stir until the reaction is sufficient; Step c, filtering, washing and drying the fully reacted solution to obtain a lithium-rich layered positive electrode material precursor with a passivated surface and a VO2 coating; Step d: heating the lithium-rich layered cathode material precursor to 400-700° C. in an inert gas atmosphere, then keeping the temperature and cooling it with the furnace to obtain a lithium-rich layered cathode material having a passivation layer and a VO2 coating layer on the surface.

2. The method for double surface modification of lithium-rich layered cathode materials according to claim 1, characterized in that: The step a also includes: A 0.1-1 mol / L vanadyl sulfate solution is prepared, and the pH value of the vanadyl sulfate solution is controlled to be 1-4.

3. The method for double surface modification of lithium-rich layered positive electrode materials according to claim 1, characterized in that: The step a comprises: Take 50-200g of lithium-rich layered positive electrode material sample, add it into 100ml of pre-prepared vanadyl sulfate solution, stir the two evenly at 50-80°C and react for 5-20 minutes.

4. The method for double surface modification of lithium-rich layered positive electrode materials according to claim 1, characterized in that: The step b comprises: Add an alkaline solution dropwise to the mixed solution until the pH value of the mixed solution is 7-10, and then continue stirring until the reaction is complete.

5. The method for double surface modification of lithium-rich layered cathode materials according to claim 4, characterized in that: The step b comprises: Add an alkaline solution dropwise to the mixed solution until the pH value of the mixed solution is 7-10, then continue stirring and react for 1-6 hours to ensure sufficient reaction.

6. The method for double surface modification of lithium-rich layered cathode materials according to claim 1, characterized in that: The step c comprises: The fully reacted solution is filtered, washed with deionized water and ethanol in turn, and then placed in a vacuum drying oven for drying to obtain a lithium-rich layered positive electrode material precursor with a passivated surface and VO2 coating.

7. The method for double surface modification of lithium-rich layered cathode materials according to claim 1, characterized in that: The step c also includes: The fully reacted solution was filtered, washed twice with deionized water and then twice with ethanol, and then placed in a vacuum drying oven and dried at 80°C to obtain a lithium-rich layered positive electrode material precursor with a passivated surface and VO2 coating.

8. The method for double surface modification of lithium-rich layered cathode materials according to claim 1, characterized in that: The step d comprises: The lithium-rich layered cathode material precursor is heated to 400-700°C at a rate of 5°C / min in an inert gas atmosphere, then kept warm for 1-6 hours and then cooled in the furnace to obtain a lithium-rich layered cathode material with a passivation layer and a VO2 coating layer on the surface.

9. The method for double surface modification of lithium-rich layered cathode materials according to claim 1, characterized in that: The alkaline solution includes one or more of sodium hydroxide solution, ammonia solution, and urea solution.

10. The method for double surface modification of lithium-rich layered cathode materials according to claim 1, characterized in that: The molecular formula of the lithium-rich layered positive electrode material is Li 1+x TM 1-x O2, wherein the TM is at least two of Ni, Co and Mn, and the value of x is 0 <x<1。

Citation Information

Cited By

  • Vanadium gradient coated lithium manganese iron phosphate, preparation method and positive electrode

    CN121439761A